Search for long-lived neutral particles in pp collisions at √s=13 TeV that decay into displaced hadronic jets in the ATLAS calorimeter - Aaboud, Morad; Andrei, George Victor; Bolz, Arthur; Dunford, Monica; Ferreira de Lima, Danilo Enoque; Franchino, Silvia; Helary, Louis; Jongmanns, Jan; Kugel, Andreas; Napolitano, Fabrizio; S̜ahinsoy, Merve; Schöning, André; et al. (The European physical journal. C, Particles and fields, 2019)
This paper describes a search for pairs of neutral, long-lived particles decaying in the ATLAS calorimeter. Long-lived particles occur in many extensions to the Standard Model and may elude searches...
ATLAS Collaboration: M. Aaboud, V.Andrei, A.E. Bolz, M. Dunford, D.E. Ferreira de Lima, S. Franchino, L. Helary, J. Jongmanns, A. Kugel, F. Napolitano, M. Sahinsoy, A. Schoening, H-C. Schultz-Coulon, T.M. Spieker, R. Stamen, P. Starovoitov, S.M. Weber, M. Wessels, X. Yue [und weitere]
Im Titel steht "s" unter dem Wurzelsymbol
Gesehen am 14.08.2020